Impact of Insurance and Treatment Regimens on HCV Outcome: Long-term Follow-up Study. (4th October 2017) - Mukka, Mallikarjuna; Akram, Sami; Koirala, Janak
Abstract: Background: Directly acting agents (DAA) have revolutionized the treatment of Hepatitis C infection. However the access to appropriate drugs has been a barrier to therapy. Our objective of this study was to find the impact of insurance type and treatment regimen on outcome in patients with hepatitis C. Methods: We have maintained a database of patients with HCV infection who were seen at our outpatient infectious disease clinic. We conducted a retrospective review of 160 patients who have been following since 2005–2006. In addition to baseline data, we also collected data on treatment status, regimens, outcome, insurance and reasons for no treatment. Statistical analyses included chi-square tests for categorical variables and ANOVA for numerical variables. This study was approved by the institutional review board. Results: Of the 160 charts reviewed, we had complete records of 40 patients who had a median follow-up period of 12 years. Among them 75% of the patients had HCV genotype 1 (1a or 1b). Liver biopsy was available only for 50% patients which showed 32.5% had early stage (0–2) and 27.5% had late stage (3–4) fibrosis. Most of the patients (17) were treated with older therapies (peg-interferon alpha with or without boceprevir or telaprevir) and 7 with newer DAA combinations, whereas 16 patients did not receive treatment. All patients with private insurance received treatment whereas a large proportion with public aid did not (100% vs. 57%, P = 0.002). Total 19 of 28 treated patients achieved a sustained viral response beyond 2 years. All 7 patients who received newer DAAs were cured. Among the 16 patients who did not receive antiviral treatment, 5 (30%) had a poor outcome including liver cirrhosis (1), hepatocellular carcinoma (2 HCC), and death (2) compared with only 2 patients (1 cirrhosis, 1 HCC) in treated group ( P <0.001). None of the patients in treated group died. Conclusion: In this study, patients who did not have access to appropriate antiviral therapy had worse outcome. The main determinant for poor access to treatment was the type of insurance. It is important to improve access to treatment for all patients with HCV infection which can reduce the rate of progression to advanced liver disease and mortality. Disclosures: All authors: No reported disclosures.